2021
DOI: 10.1093/cid/ciab670
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Healthcare-Associated Transmission of Sever Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in Hospitalized Cancer Patients

Abstract: Background There is limited information on the risk of hospital-acquired COVID-19 among high-risk hospitalized patients after exposure to an infected patient or healthcare worker (HCW) in a non-outbreak setting. Methods This study was conducted at a tertiary care cancer center in New York City from March 10, 2020, until February 28, 2021. In early April 2020, the study institution implemented universal SARS-CoV-2 testing at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
1
19
2
Order By: Relevance
“…This proportion is consistent with household transmission rates between spouses (37.8%, 95% CI 25.8%-50.5%) 17 and other reports on transmission between hospital roommates (up to 39%). 18,19 Although only 45/254 (17.7%) of cases of HA-SARS-CoV-2 infection in our study were directly linked to transmission between patients in a multi-bed room, more HA cases might be indirectly linked to high population density. 7 The importance of crowding on COVID-19 incidence and mortality has already been shown in Canadian long-term care settings.…”
Section: Discussioncontrasting
confidence: 52%
“…This proportion is consistent with household transmission rates between spouses (37.8%, 95% CI 25.8%-50.5%) 17 and other reports on transmission between hospital roommates (up to 39%). 18,19 Although only 45/254 (17.7%) of cases of HA-SARS-CoV-2 infection in our study were directly linked to transmission between patients in a multi-bed room, more HA cases might be indirectly linked to high population density. 7 The importance of crowding on COVID-19 incidence and mortality has already been shown in Canadian long-term care settings.…”
Section: Discussioncontrasting
confidence: 52%
“…A separate study found a secondary attack rate for hospitalized roommates of 18.9% overall and 35.7% in the setting of AGPs. 86 The attack rate in these scenarios mirrors that observed in household settings. 11 , 12 , 13 , 87 Infections among patients have also been observed in inpatient psychiatric units where it is difficult to promote mask wearing, distancing, and hand hygiene, and group activities are instrumental to treatment.…”
Section: Transmission In Healthcare Settings and Lessons Learnedmentioning
confidence: 56%
“…Patient-to-patient transmission in the setting of roommates in semi-private accommodations in healthcare facilities has been directly studied. 85 , 86 In one report over 7 months at an acute care hospital, there were 31 exposed patient roommates, 39% of whom ultimately tested positive for SARS-CoV-2. 85 The beds were 5 feet apart side-by-side and 7 feet apart mid-pillow to mid-pillow with a closed curtain between them.…”
Section: Transmission In Healthcare Settings and Lessons Learnedmentioning
confidence: 99%
“… 2 Finally, there is evidence that transmission of SARS-CoV-2 may occur in areas of healthcare facilities with adequate ventilation. 12 For example, Chow et al 12 reported frequent transmission of SARS-CoV-2 from patients with unsuspected COVID-19 to roommates, particularly if aerosol-generating procedures were performed. Thus, adequate ventilation based on carbon dioxide measurements should not provide complete reassurance that airborne transmission will not occur.…”
Section: Discussionmentioning
confidence: 99%